The local and provincial archival collections on Java from the colonial era; The preliminary results of the inventorization project - Dwiandari, Nadia F.; van Langen, Johan (Wacana, Journal of the Humanities of Indonesia, 2019)
The National Archives of Indonesia (Jakarta) and the National Archives of the Netherlands (The Hague) have been collaborating on the Java Archival Guide Project. This project, which initially ran from 2016 to 2017, will be continued in a second phase. It will provide insight into the size and richness of the local and provincial archives formed on Java during the colonial period after the dissolution of the Dutch East India Company (1800-1949). The whereabouts of these archives in Indonesia have been unknown to many researchers, preventing access to academics, local historians, and family researchers. The collections encountered during the research for this project date from the last days of the Dutch East India Company to the Japanese invasion and the years of the Indonesian National Revolution. The completed phase of the project was limited to the repositories of local and provincial governmental agencies on Java. In some cases the colonial collections seem to have disappeared, and in others, the records seem to have survived the years almost intact.